Exploring the flexibility of Polish family farms during transition - Agata Pieniadz; Swetlana Renner; Lech Goraj (Zagadnienia Ekonomiki Rolnej = Problems of Agricultural Economics, 2010)
Based on farm panel data we empirically investigate the determinants of Polish farm households' flexibility from 1994 to 2001. We focus on scale flexibility (adjustment in production volume) and scope flexibility (adjustment in product mix). The findings of our fixed-effects regression provide evidence that smaller farms are more flexible, both with regard to scale and scope of production. Farms with a higher share of variable costs tended to be more flexible, while producers who specialized in capital-intensive technologies turned out to be less flexible. Some results differ significantly from the prevailing expectations, in particular we found that farms where a generational succession took place displayed less flexibility over time. Moreover, access to off-farm income and finances have opposite effects on scale and scope flexibility. An explanation for these outcomes may be the varying term structure of liquidity sources. There are relevant differences in the strategies Polish farmers used to adjust to changing environmental conditions during transition, which should be taken into account in the design of supporting policies.
Keywords: 330; agricultural economics; structural change; flexibility; family farms; transition; adjustment; Poland